UPAYA MENINGKATKAN LITERASI MEMBACA DI MASA PANDEMI MELALUI KEGIATAN SEMINGGU SEBUKU - Siti Habsari Pratiwi (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2021)
Reading literacy skill is related to one’s ability to analytically and critically understand the reading text. Reading literacy is not only related to knowledge and skills but also motivation, attitudes and behaviour. During the pandemic, the use of digital apps plays a critical role;. This situation also led to the emergence of a reading literacy community called ‘a week a book’ community through digital media. This community has 232 members where everyone reads a book every week. At the end of the week, the volunteers reflected on the book they read and submitted through the application. This kind of circulation enabled everyone in the community to listen to the others’ review anywhere. This reading literacy community was initiated by sociopreneur.id. This study will focus on the phenomenon of reading literacy in the sociopreneur.id application related to activities and their contribution to reading literacy during a pandemic. This activity has a positive effect on reading interest, independence, social interaction, and the reading practice of members to increase.